ANALISIS PENGARUH KOMPENSASI, DISIPLIN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA KARYAWAN PADA PT INDO MEGA BERJAYA MEDAN - simbolon, dwi maria (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2021)
The objective of this research is to know the influence of compensation, work discipline and work commitment towards working performance at PT Indo Mega Berjaya Medan. This research was conducted at PT. Indo Mega Berjaya, Medan. This research uses descriptive and quantitative research methods. The subject of this research uses the PT. Indo Mega Berjaya Medan with a population of 128 employees and the sampling technique using simple random sampling technique in order to obtain a sample of 56 respondents. The instrument used was a questionnaire to collect data on the variables of compensation, work discipline, work commitment and employee performance Data analysis techniques used are validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, multiple linear correlation coefficient test, t test or partial hypothesis test, F test or simultaneous test and coefficient calculation. determination. The results of descriptive analysis in the variables of compensation, work discipline, work commitment and employee performance are in good categories. Based on a partial analysis of compensation, work discipline and work commitment have a positive and significant effect on employee performance at PT. Indo Mega Berjaya Medan. Simultaneously the variable compensation, work discipline, work commitment and employee performance have a positive and significant influence on employee performance at PT. Indo Mega Berjaya Medan. From the results of the test of the determination deficiency, the r value obtained is 64.4%. The remaining 35.6% is influenced by other variables not examined in this study such as motivation, work environment, leadership, and so on